2016
DOI: 10.1007/s40071-016-0141-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Henna (Lawsonia inermis) extract on the immunity and survival of common carp, Cyprinus carpio infected with Aeromonas hydrophila

Abstract: In this study, the immunomodulatory properties of Lawsonia inermis (henna) in common carp, Cyprinus carpio was investigated. Fish were intraperitoneally (i.p.) injected with 6, 60 or 600 mg kg -1 body weight (BW), of the methanolic soluble fractions of L. inermis. The extract at 60 and 600 mg kg -1 BW, significantly (p \ 0.05) enhanced some non-specific immune parameters such as serum lysozyme and bactericidal activity, phagocytic and respiratory burst activity, total leucocyte count (TLC), lymphocyte, monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 57 publications
9
10
0
Order By: Relevance
“…In the present study, the highest lysozyme activity was observed in the concentration of high dose treatment. Similar to our results, evaluation of lysozyme activity has been reported with thoodhuvalai (Solanum trilobatum) and heart‐leaved moonseed (Tinospora cordifolia) in Mossambique tilapia, Oreochromis mossambicus (Alexander, John Wesly Kirubakaran, & Michael, ; Divyagnaneswari, Christybapita, & Michael, ); holy Basil ( Ocimum sanctum) in rohu, Labeo rohita (Das, Raman, Saha, & Singh, ); peppermint (Mentha piperita) in Caspian brown trout, Salmo trutta caspius (Adel, Safari, Pourgholam, Zorriehzahra, & Esteban, ); henna (Lawsonia inermis) in common carp (Soltanian & Fereidouni, ); Excoecaria agallocha and Chinese mahogany ( Toona sinensis) in Nile tilapia, Oreochromis niloticus (Laith et al, ; Wu, Liu, Chang, & Hsieh, ), and common dandelion (Taraxacum officinale) and common hawthorn (Crataegus monogyna) in golden pompano, Trachinotus ovatus (Tan, Sun, Chen, et al, ; Tan, Sun, Huang, et al, ). Similar results were noted in common carp fed diets enriched with turmeric powder, Curcuma longa (Abdel‐Tawwab & Abbass, ), or Nile tilapia fed diets enriched with green tea, Camellia sinensis (Abdel‐Tawwab et al, ), American ginseng, Panax quinquefolium (Abdel‐Tawwab, ), or cinnamon ( Cinnamomum zeylanicum ) nanoparticles (Abdel‐Tawwab et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the highest lysozyme activity was observed in the concentration of high dose treatment. Similar to our results, evaluation of lysozyme activity has been reported with thoodhuvalai (Solanum trilobatum) and heart‐leaved moonseed (Tinospora cordifolia) in Mossambique tilapia, Oreochromis mossambicus (Alexander, John Wesly Kirubakaran, & Michael, ; Divyagnaneswari, Christybapita, & Michael, ); holy Basil ( Ocimum sanctum) in rohu, Labeo rohita (Das, Raman, Saha, & Singh, ); peppermint (Mentha piperita) in Caspian brown trout, Salmo trutta caspius (Adel, Safari, Pourgholam, Zorriehzahra, & Esteban, ); henna (Lawsonia inermis) in common carp (Soltanian & Fereidouni, ); Excoecaria agallocha and Chinese mahogany ( Toona sinensis) in Nile tilapia, Oreochromis niloticus (Laith et al, ; Wu, Liu, Chang, & Hsieh, ), and common dandelion (Taraxacum officinale) and common hawthorn (Crataegus monogyna) in golden pompano, Trachinotus ovatus (Tan, Sun, Chen, et al, ; Tan, Sun, Huang, et al, ). Similar results were noted in common carp fed diets enriched with turmeric powder, Curcuma longa (Abdel‐Tawwab & Abbass, ), or Nile tilapia fed diets enriched with green tea, Camellia sinensis (Abdel‐Tawwab et al, ), American ginseng, Panax quinquefolium (Abdel‐Tawwab, ), or cinnamon ( Cinnamomum zeylanicum ) nanoparticles (Abdel‐Tawwab et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…TLC and neutrophil are indicators of humoral or nonspecific immunity and significant increase in TLC enhances the humoral immune response as Neutrophil activates on entry of any pathogen (mainly bacteria) in the body with in 24 hrs. Our findings are supported by previous investigations [28][29][30][31][32] indicating the ability to stimulate the immune system. However, no significant difference was observed in all the groups for lymphocytes, eosinophils and monocytes.…”
Section: Effect Of L Inermis Linn Leaves On Bodysupporting
confidence: 93%
“…Similar improvements in serum bactericidal activity were reported in Nile tilapia fed on Excoecaria agallocha (Laith et al, ). Moreover, administration of Ixora coccinea in ornamental goldfish, Carassius auratus (Anusha, Thangaviji, Velmurugan, Michaelbabu, & Citarasu, ) and Henna, Lawsonia inermi s, in common carp (Soltanian & Fereidouni, ) induced increased serum killing activity.…”
Section: Discussionmentioning
confidence: 99%